The practice of physical and sporting activity in teenagers with idiopathic scoliosis is related to the curve type - Meyer, C.; Haumont, T.; Gauchard, G. C.; Leheup, B.; Lascombes, P.; Perrin, Ph. P. (Scandinavian journal of medicine & science in sports, 2008)
Idiopathic scoliosis (IS) is correlated with a muscular disequilibrium of the spine and an alteration of balance control, efficient performance of the latter being necessary for physical and sporting activities (PSA). However, the type of the IS curve has different effects on muscle and on balance control according to the primary curve location. This study aimed to determine the relationships between IS type and PSA practice. One hundred and sixty‐nine girl adolescents with IS [double major curve (DMC) scoliosis: n=74; single major curve (SMC) scoliosis: n=95] and 100 age‐matched control girl adolescents completed an epidemiological questionnaire informing on curricular and extracurricular PSA. Adolescents with DMC scoliosis practised more PSA than those with SMC scoliosis. Moreover, among all PSA referenced, gymnastic activities are the most practiced PSA both in IS teenagers, whatever the curve type, and in controls. Besides, teenagers practising gymnastics were more numerous in those with DMC scoliosis than those with SMC scoliosis and controls. The highest proportion of adolescents with DMC scoliosis practising PSA, especially gymnastics, could be linked to the fact that they are less subject to scoliosis‐related biomechanical repercussions leading to a better balance control, which is essential in these PSA.